Development of Virtual Lab Integrating Ethnoscience in Project-Based Inquiry Learning Tools to Enhance Creative Thinking Skills - Nursamsu, Nursamsu; Nurhafidhah, Nurhafidhah; Prabowo Warsodirejo, Pandu (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to develop and test the validity and practicality of a Project-Based Inquiry Virtual Lab learning tool integrated with ethnoscience to improve students' creative thinking skills. The study used the Research and Development (R&D) method with the ADDIE development model. Data were collected using expert validation sheets and practicality questionnaires for teachers and students, and analyzed using quantitative descriptive methods. The learning tool was rated very valid with an average score of 82.52%, covering aspects of content, construction, language, and display. The practicality test showed that the tool was very practical, with average scores of 86.9% from teachers and 85.5% from students. These findings indicate that the developed learning tool is feasible to use, easy to implement, and has the potential to be effective in improving students' creative thinking skills.